The Effects of Consistency and Inconsistency in the Source Features of WeChat Tweets on Older Chinese Adults’ Intentions to Adopt Personal Information Security Knowledge - Yu Zhang; Qian Zhang (Social Media + Society)
WeChat tweets have become an important way to spread knowledge of the importance of personal information security and to enhance older Chinese adults’ awareness of information security. Based on the knowledge adoption model and the elaboration likelihood model, this study identifies two types of tweets’ source features, that is, publisher type (official or unofficial) and author type (expert or non-expert). In addition, based on cognitive fit theory, this study explores the effects of the consistency and inconsistency between the two types of source features on the knowledge adoption intentions of older Chinese adults. The proposed research model is validated by carrying out a 2 × 2 between-subjects experiment, which also takes into account the three control variables of: “amount of readership,” “gender,” and “the perceived credibility of WeChat.” The results show that, compared with non-official tweets or non-expert tweets, official tweets or expert tweets are more conducive to enhancing older adults’ perception of the credibility and usefulness of the tweets and thus improve their knowledge-adoption intentions. However, the inconsistent combinations of unofficial and expert tweets and official and non-expert tweets can weaken the positive impact of official or expert sources on perceived credibility and usefulness. In addition, as the older adults’ perception of the relevance to themselves of personal information security increases and as their ability to process tweets strengthens, the influence of source features on perceived credibility and usefulness diminishes.